2012
DOI: 10.1001/archinternmed.2012.2177
|View full text |Cite|
|
Sign up to set email alerts
|

Patient Preference in the Decision to Place Implantable Cardioverter-Defibrillators

Abstract: fect, guidelines should consistently emphasize the importance of patient preferences in all clinical decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Prior studies have suggested that clinicians weigh guidelines and mortality data to be more important than patients’ preferences in their recommendations for ICDs. 6 In a related study, physicians also used very strong language in their recommendations for ICDs, 5 and as a consequence, patients often did not feel fully informed. 7 Our findings expand upon this prior work by using contemporary theories from psychology to provide depth and specificity regarding mechanisms behind how varying communication strategies can influence decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have suggested that clinicians weigh guidelines and mortality data to be more important than patients’ preferences in their recommendations for ICDs. 6 In a related study, physicians also used very strong language in their recommendations for ICDs, 5 and as a consequence, patients often did not feel fully informed. 7 Our findings expand upon this prior work by using contemporary theories from psychology to provide depth and specificity regarding mechanisms behind how varying communication strategies can influence decisions.…”
Section: Discussionmentioning
confidence: 99%
“…5 A survey of cardiologists suggested that mortality data and guidelines were more important than patient preferences or patient knowledge in their recommendations for ICDs. 6 A review of studies of patients’ perceptions suggested that physicians generally employed a paternalistic approach to the decision to receive an ICD and patients often felt uninformed. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Another study identified that physicians were frightened to tell the patients too many of the risks because they didn't want them to make a “bad decision.” 69 A survey of over 1200 members of the American College of Cardiology noted that physicians rated guidelines and mortality data much higher than patient preferences or patient knowledge in their recommendations for ICDs. 71 …”
Section: Current Knowledgementioning
confidence: 99%
“…In the case of ICDs, current evidence suggests that patients are not as informed as they should be with evidence suggesting disempowered patients 36 and paternalistic physicians who think their patients’ preferences do not matter. 37 Anticipated adverse events and the possibility of rare unexpected events should be reviewed. Information including statistics is difficult for patients to assimilate; use of natural frequencies instead of percentages such as “If we put this in 100 patients like you, we would expect….” may facilitate understanding.…”
Section: Fate Of Cardiac Devices Intended To Prolong Lifementioning
confidence: 99%